DAYA TARIK OBJEK WISATA AIR PUTRI WAIYOHO DI DESA KAWA KABUPATEN SERAM BAGIAN BARAT - Siregar, Wilsa Noni; Lelloltery, Henderina; Seipalla, Billy (MARSEGU : Jurnal Sains dan Teknologi, 2024)
The purpose of this study is to examine the appeal of the Air Putri Waiyoho tourist attraction and visitors' perceptions of Air Putri Waiyoho in Kawa Village, West Seram Regency. This research uses a survey method to assess the viability of the tourist attraction's potential, based on criteria from the Guidelines for Operational Area Analysis of Nature Tourism Attractions (ADO-ODTWA) by the Directorate General of Forest Protection and Nature Conservation (PHKA) in 2003, and qualitative descriptive analysis to understand visitor perceptions, with a sample of 77 visitor respondents interviewed.The main attraction at Air Putri Waiyoho is the fresh water spring in a bathing pool with clear, bright water surrounded by lush trees, enhancing the appeal for tourism activities. Based on the Tourism Feasibility Index analysis, the attraction criteria score 80.95%, accessibility criteria score 72.2%, and visitor facilities and infrastructure criteria score 66.6%. Thus, the feasibility analysis places Air Putri Waiyoho as a high-category tourist attraction. Visitor perceptions indicate a 100% attraction appeal, available facilities at 90.91%, and accessibility with 48% noting ease of transportation and reachability.